Antifungal Activity of the Ethyl Acetate Fraction of Matoa Leaves (Pometia pinnata J. R. Forst & G. Forst) Against Trichophyton rubrum - Tika Afriani; Devahimer Harsep Rosi; Reka Cania (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Dermatophytosis is a prevalent skin infection in tropical regions like Indonesia, predominantly caused by the fungus Trichophyton rubrum. While Matoa leaves (Pometia pinnata) are known for their medicinal properties, their specific antifungal potency requires optimization through fractionation. This study aimed to evaluate the antifungal activity of the ethyl acetate fraction of Matoa leaves and determine its effective concentration against T. rubrum. This experimental study employed the disc diffusion method using Sabouraud Dextrose Agar (SDA). The ethyl acetate fraction was tested at concentrations of 10% and 20%, with 2% Ketoconazole as the positive control and DMSO as the negative control. The results demonstrated that the ethyl acetate fraction exhibited strong antifungal activity, yielding inhibition zones of 18.25 mm at 10% concentration and 19.75 mm at 20% concentration. Statistical analysis using the Kruskal-Wallis and Mann-Whitney tests indicated significant antifungal activity compared to the negative control (p < 0.05), though no significant difference was observed between the 10% and 20% concentrations. These findings suggest that the semi-polar ethyl acetate fraction of Matoa leaves is a potent natural antifungal agent, showing strong efficacy even at lower concentrations.